1981
DOI: 10.1002/hlca.19810640121
|View full text |Cite
|
Sign up to set email alerts
|

New Dienophiles: 1‐Acetylvinyl Arenecarboxylates. Reactivity toward cyclopentadiene and exocyclic dienes

Abstract: SummaryThe preparations of 1-acetylvinyl arenecarboxylates H2C=C (COCH,)OCOR with R = phenyl, p-nitrophenyl, 2,4-dinitrophenyl, u -and P-naphthyl are described (3). The Diels-A Ider reactivity of these dienophiles toward cyclopentadiene is evaluated and compared with that of methyl vinylketone, 3-trimethylsilyloxy-, 3-ethoxy-and 3-acetoxy-3-buten-2-ones. The stereoselectivity of the cycloadditions of these dienophiles with 2,3,5,6-tetramethylidene-7-oxanorbornane (1) and 5,sdimethoxy-l,4-epoxy-2,3-dimethyliden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…The steric hindrance and the hyperconjugative effect of the alkyl group in the double bond might be responsible for the lower reactivity of the former dipolarophiles 4f,6,16. The faster addition of 12c towards 7a , in comparison with those of 12a and 12b , agrees with the observation that electron‐withdrawing groups in the aroyloxy group of captodative olefins 1 increase the reaction rate in concertedDiels–Alder additions 13a…”
Section: Resultssupporting
confidence: 71%
“…The steric hindrance and the hyperconjugative effect of the alkyl group in the double bond might be responsible for the lower reactivity of the former dipolarophiles 4f,6,16. The faster addition of 12c towards 7a , in comparison with those of 12a and 12b , agrees with the observation that electron‐withdrawing groups in the aroyloxy group of captodative olefins 1 increase the reaction rate in concertedDiels–Alder additions 13a…”
Section: Resultssupporting
confidence: 71%
“…Indeed, the reactivity was enhanced by the presence of an electron-withdrawing group [20]. This is in agreement with previous results where the enones acted as dienophiles in Diels -Alder additions under conditions of normal electron-demand [15]. Such a behavior in enones 1 was mostly associated with the remote inductive effect (I) of the substituent in the aroyloxy group, in which the reactivity is increased with ÀI groups [14].…”
Section: Hetero-diels -Alder Reactions Of Captodative Olefins With Alsupporting
confidence: 90%
“…The positions of the H-atoms were kept fixed with a common isotropic displacement parameter. Data for 7a: Formula C 15 CCDC-680887 contains the supplementary crystallographic data (excluding structure factors) for the structure of 7a. These data can be obtained, free of charge, via www.ccdc.ac.uk/data_request/cif.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…An analogous correlation can be done with the LUMOs of the olefins. From the data listed in Tables and , it is apparent that 1a should be more reactive than MVK; nevertheless, the kinetic data have shown that MVK is about 2.6 times more reactive than 1a …”
Section: Resultsmentioning
confidence: 98%